2015
DOI: 10.1186/s12903-015-0148-x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcomes of single-visit versus multiple-visit non-surgical endodontic therapy: a randomised clinical trial

Abstract: BackgroundClincians have been providing single-visit and multiple-visit endodontic treatments for their patients. This study aims to compare the success rate, prevalence of postoperative pain and chairside time of single-visit and multiple-visit endodontic treatments.MethodPatients who required primary endodontic treatment in a university dental clinic were randomly allocated to two general dentists for single-visit or multiple-visit treatments using the same materials and procedures. Ni-Ti rotary files were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
48
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 34 publications
6
48
0
7
Order By: Relevance
“…Thus the post-obturatuion pain was fairly recorded in few cases after one day but that it mostly subsided after one week. This was corroborated with several studies, where they reported that the cases recorded post-operative pain was recorded after 24 hours, the majority of patients in both groups reported no pain or only minimal pain, and pain disappeared after one week of treatment (12)(13)(14) .…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Thus the post-obturatuion pain was fairly recorded in few cases after one day but that it mostly subsided after one week. This was corroborated with several studies, where they reported that the cases recorded post-operative pain was recorded after 24 hours, the majority of patients in both groups reported no pain or only minimal pain, and pain disappeared after one week of treatment (12)(13)(14) .…”
Section: Discussionsupporting
confidence: 75%
“…Patients experiences less frequency of post-obturation pain after single-visit than those having multiple-visits root canal retreatment. These results corroborated the results of many studies (12)(13)(14)29) .But disagreed with a study reported that the two visits root canal retreatment was more effective in completely eliminating post-operative pain than the single visit technique, however they used variable treatment procedures, and most of cases were treated in two or more appointments (18) .…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…observed in all the patients, so this radiographic evaluation cannot be associated with the failure of root canal therapy. 14 According to Prashant et al, however, it is necessary to acknowledge the fact that a period of 6 weeks is too short a period for radiographic evaluation to draw any confirm conclusion regarding the outcome of treatment. The resolution of periapical rarefactions in this study supports the results of the present study.…”
Section: Radiographic Evaluation Of Periapical Rarefactions Till 18-mmentioning
confidence: 99%
“…Wong et al questioned the persistent apical radiolucency over 20 years as absolute failure. 14 In the current study, postoperative complications like pain, tenderness to percussion, and swelling at 6-week follow-up, and radiographic changes after 18 months follow-up were assessed.…”
Section: Radiographic Evaluation Of Periapical Rarefactions Till 18-mmentioning
confidence: 99%